2022
DOI: 10.1158/2159-8290.cd-21-0032
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fragmentation Triggers Ineffective Hematopoiesis in Myelodysplastic Syndromes

Abstract: Ineffective hematopoiesis is a fundamental process leading to the pathogenesis of myelodysplastic syndromes (MDS). However, the pathobiological mediators of ineffective hematopoiesis in MDS remain unclear. Here, we demonstrated that overwhelming mitochondrial fragmentation in mutant hematopoietic stem cells and progenitors (HSC/P) triggers ineffective hematopoiesis in MDS. Mouse modeling of CBL exon deletion with RUNX1 mutants, previously unreported comutations in patients with MDS, recapitulated not only clin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…In a previous study, AML patients with high FIS1 expression likely to be chemotherapy-resistant and were more frequently M0/M1 FAB subtypes [77]. Similarly, mitochondrial fragmentation and increased Drp1 is also associated with MDS with CBL exon deletion and RUNX1 mutation, promoting dysplasia and impaired granulopoiesis [120]. Additionally, Drp-1-dependent mitochondrial fragmentation is seen in the mesenchymal stromal cells in MDS with iron overload, contributing to cell damage [121].…”
Section: Mds Aml and Mitochondrial Dynamics Mitochondrial Transfermentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, AML patients with high FIS1 expression likely to be chemotherapy-resistant and were more frequently M0/M1 FAB subtypes [77]. Similarly, mitochondrial fragmentation and increased Drp1 is also associated with MDS with CBL exon deletion and RUNX1 mutation, promoting dysplasia and impaired granulopoiesis [120]. Additionally, Drp-1-dependent mitochondrial fragmentation is seen in the mesenchymal stromal cells in MDS with iron overload, contributing to cell damage [121].…”
Section: Mds Aml and Mitochondrial Dynamics Mitochondrial Transfermentioning
confidence: 92%
“…In a mouse model with both RUNX1 mutation and CBL exon deletion increased Drp1-dependent mitochondrial fission and ROS production in the tumor cells, leading to impaired granulopoiesis dysplasia and an overall MDS phenotype. These changes were reversible with Drp1 inhibition, making it a promising therapeutic candidate in MDS patients harboring RUNX1 mutation/RUNX1/RUNX1T1 fusion gene [120].…”
Section: Runt-related Transcription Factor 1 (Runx1)mentioning
confidence: 99%
“…We next analyzed the mitochondrial morphology in HSPCs. Alterations in mitochondrial morphology and distribution in HSCs have been previously reported in myelodysplastic syndrome (MDS) and leukemia; mitochondria in HSCs from MDS models diffuse and spread out while mitochondria in leukemic stem cells (LSC) exhibit polarity and are concentrated ( 16 , 17 ). Imaging flow cytometer (IFM) was utilized to calculate mitochondrial area, concentration, and polarity in individual HSPCs.…”
Section: Resultsmentioning
confidence: 96%
“…In a mouse model of CBL exon deletion with RUNX1 mutants, that recapitulated clinically relevant MDS phenotypes, HSC and progenitor cells exhibited excessive mitochondrial fragmentation that was caused by enhanced activity of the mitochondrial fission regulator DRP1. The subsequent elevation in ROS production and inflammatory signals promoted the development of dysplasia and impaired granulopoiesis ( 18 ). Other studies have reported abnormal mitochondrial structure, or abnormal mitochondrial biogenesis and mitophagy in BMF, notably in FA.…”
Section: Abnormal Mitochondrial Dynamics Contributes To Mdsmentioning
confidence: 99%
“…Interestingly, several evidence suggest that disruption of mitochondria is another preponderant factor in BMF/MDS development. Abnormal mitochondria have been linked to both acquired and hereditary BMF (18)(19)(20)(21)(22)(23)(24). Patients with MDS have transcriptional, morphological and functional dysregulation of their mitochondria, according to several studies (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%